A new four‐row integral transposition method of stator windings and circulating current loss reduction in large turbo generators. Issue 1 (2nd November 2022) - Zhang, Linlin; Liang, Yanping
Abstract: Transposition of stator windings for large turbo generators is a key technology. At present, the stator windings with four‐row strands for large turbo generators are usually transposed on both sides of the slot centreline and connected at the end by the joint sleeve. The different transposition methods of strands have an important effect on strand currents, circulating currents, and circulating current losses. A new four‐row integral transposition method is proposed in this study. Several transposition methods based on the four‐row integral transposition method are compared with the double Roebel transposition methods using 3‐D time‐harmonic field. The 3‐D model without the end and with the end are both calculated. The results show that the four‐row integral transposition method has an obvious advantage in reducing circulating current loss. Finally, a 2‐D finite element model of transient magnetic field is calculated and its calculation results further support for the effectiveness of the proposed transposition method. The proposed transposition method has a great application value, which can reduce additional loss, avoid partial overheating and short circuit fault of stator windings in large turbo generators.